Incomplete TCRβ allelic exclusion accelerates spontaneous autoimmune arthritis in K/BxN TCR transgenic mice - Auger, Jennifer L. (2012)
Allelic exclusion of antigen receptor loci is a fundamental mechanism of immunological self tolerance. Incomplete allelic exclusion leads to dual T cell receptor (TCR) expression and can allow developing autoreactive αβ T lymphocytes to escape clonal deletion. Because allelic exclusion at the TCRβ locus is more stringent than at the TCRα locus, dual TCRβ expression has not been considered a likely contributor to autoimmunity. We show here that incomplete TCRβ allelic exclusion permits developing thymocytes bearing the autoreactive, transgene-encoded KRN TCR to be positively selected more efficiently, thereby accelerating the onset of spontaneous autoimmune arthritis. Our findings highlight dual TCRβ expression as a mechanism that can enhance the maturation of autoreactive pathogenic T cells and lead to more rapid development of autoimmune disease.